Tradable planning permits for land-use control in Germany. - Henger, Ralph; Bizer, Kilian (My University, 2008)
Die Bundesregierung hat sich mit der Nationalen Nachhaltigkeitsstrategie dazu verpflichtet, das Siedlungs- und Verkehrsflächenwachstum in Deutschland von 115 ha (2001 2004) auf 30 ha pro Tag bis zum Jahr 2020 zu senken und gleichzeitig eine Reihe weiterer qualitativer Flächenentwicklungsziele formuliert. Das markbasierte Steuerungsinstrument der handelbaren Flächenausweisungsrechte bietet hierfür eine kosteneffiziente und ökologisch wirksame Zielerreichungsoption. In diesem Cap-and-Trade System wird das Flächenausweisungsverhalten der Kommunen direkt gesteuert. Der Mengencap bezieht sich auf den Gesamtumfang der neu in Anspruch genommen Flächen während der Handel (Trade) den Gemeinden den Zu- und Verkauf von Ausweisungsrechten gestattet. Diskutiert werden die Bedingungen einer ökonomisch effizienten und ökologisch effektiven Umsetzung quantitativer als auch qualitativer Ziele.

The German Federal Government has committed itself to reducing the growth of settlement and traffic areas from 115 hectares (2001 2004) to 30 hectares per day by 2020 in addition to a broad range of qualitative land development objectives. In order to achieve a cost-effective solution, this paper suggests a cap-and-trade system of tradable planning permits that control municipalities in their land development activities. The cap refers to the explicit limit on land development while trading allows municipalities to sell or buy planning permits they do not use themselves. We discuss the general conditions for a cost-effective and ecologically effective realization of quantitative as well as qualitative land-use targets. As land development bears similar characteristics to a non-uniformly mixed pollutant we present some fundamentals of tradable permit systems, focusing on the spatial pattern of environmental damages and the difficulties in implementing them. We present three administratively feasible tradableplanning permit approaches to landuse control: an undifferentiated permit system, a trading-ratio system and variations of zonal permit systems. We apply criteria, including efficiency gains, ecological effectiveness, hot spot formation and transaction costs, which enable a critical evaluation of alternative options for a tradable planning permit system in general.
Keywords: Flächenverbrauch; Flächennutzung; Siedlungsfläche; Verkehrsfläche; Zersiedelung; Lösungsansatz; Handlungskonzept; Flächenmanagement; Bodenfunktion; Flächensteuerung; Kontrolle; Zertifizierung